Chemical constituents from the fungus Chaetomium cupreum RY202 - Panthama, Natcha; Kanokmedhakul, Somdej; Kanokmedhakul, Kwanjai; Soytong, Kasem (My University, 2015)
Two new angular types of azaphilones, isochromophilonol (1) and ochrephilonol (2), together with ten known compounds (3-12), were isolated from Chaetomium cupreum RY202. Their structures were established on the basis of spectroscopic data and the absolute configurations of 1 and 3 were determined by the modified Mosher's method. Compounds 1, 2 and 4 showed moderated cytotoxicity against KB and NCI-H187 cell lines (IC50 9.63-32.42 μg/mL).
Keywords: Azaphilone; Cheaetomium; Cheaetomium cupreum; Cytotoxicity